Hot Water Looping System to Control Temperature of Drug Production Based Arduino - I Dewa Made Juniarta Putra; Indah Sulistiyowati; Syamsudduha Syahrorini (Universitas Muhammadiyah Sidoarjo, 2022)
The temperature regulation in the drug production room is intended as a way to maintain the quality of the drug in accordance with the Good Manufacturing Practices (CPOB). In order to regulate the room temperature, one of the supporters is hot water. So a looping hot water system is needed which will be circulated to the AHU (Air Handling Unit) machine. To get hot water that is circulated automatically, a looping hot water system is made. This control system is made using Arduino Uno as a controller for the looping hot water system which will later control all supporting devices, the HC-SR04 ultrasonic sensor to read the water level in the tank, the DS18B20 sensor to read the water temperature, 16x2 LCD, 4x4 keypad, relays, heating components and a pump to fill the water tank automatically and circulate hot water. From the test results of installing this system with 5 times of data collection, it can be seen that the process of filling the water tank, water heating, and water circulation is going well with the accuracy of the ultrasonic sensor HC-SR04 reaching 96% and the DS18B20 sensor having an accuracy rate of up to 97%. Results This can make the drug production process run well because the room temperature is maintained.